PENGARUH AGRESIVITAS PAJAK, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2015) - Rizky Amalia Wardhani; Dul Muid (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to examine the influence of tax aggressiveness, size and profitability with corporate social responsibility. Independent variabel used in this research is the tax aggressiveness, size and profitability. Dependent variabel in this research is corporate social responsibility. This research used three control variables, they are leverage, capital intensity and market to book ratio.This research population was manufacture companies listed on Indonesian Stock Exchange during 2014-2015. The sample of the research is chosen by using purposive sampling method. Total samples used in this study as many as 153 companies.  Data then analyzed using ordinary least square regression. This research showed that the aggressiveness of corporate taxes and size significantly and positively related to CSR. This result accordance with legitimacy theory. But, profitability not related to corporate social responsibility.